Investigating the role of spatial frequency bands in drawing - Freeman, Tyler E. (Kansas State University, 2009)
To investigate the role of various bands of spatial frequencies for drawing, untrained artists drew four portraits from four different bands of spatial frequencies (e.g. unfiltered, 4-8, 8-16, & 16-32 cycles per face width (c/fw)). Raters then judged the accuracy of the drawings in comparison to both the source image from which the drawings were produced and an unfiltered version of the same face. The results show that low spatial frequencies (LSFs) and high spatial frequencies (HSFs) were useful for drawing, relative to middle spatial frequencies (MSFs). Additionally, the unfiltered condition that contained all spatial frequencies produced the most accurate drawings. This suggests that when artists are allowed access to both LSFs and HSFs they are able to utilize the global structure information carried in LSFs as well as the edge and detail information carried in HSFs to create more accurate drawings. The author posits that the MSFs that are useful for face recognition become redundant for drawing and that novice artists discount these MSFs in the control condition in order to increase the saliency and usefulness of the LSFs and HSFs. The results have implications for art education, drawing technology and the development of low-level drawing theory.
Keywords: Art; Drawing; Face Perception; Spatial Frequency; Spatial Vision; Psychology, Cognitive (0633)